Harmonic Properties of Gauss Mappings in H^3 - Masal'tsev, L. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider some harmonic mappings related to hyperbolic Gauss mappings and Gauss mappings in the Obata sense.